Quantitative Analysis of Multivalent Ligand Presentation on Gold Glyconanoparticles and the Impact on Lectin Binding - Wang, Xin (2010)
Glyconanomaterials, nanomaterials carrying multiple carbohydrate ligands, provide an excellent platform for sensitive protein recognition. Using nanomaterials as the scaffold, multivalent interactions between glycan ligands and proteins have been demonstrated. However, the quantitative analysis of the binding affinity of these glyconanomaterials has been lacking. In this article, we report a new method to measure the binding affinity of glyconanoparticle (GNP)-protein interactions based on a fluorescent competition binding assay, which yielded the apparent dissociation constant (K(d)) of GNPs with the interacting protein. Au nanoparticles conjugated with underivatized mono-, oligo-, poly-saccharides were synthesized using our recently developed photocoupling chemistry. The affinities of these GNPs with lectins were measured and were several orders of magnitude higher than the corresponding free ligands with lectins. The effect of ligand display on the binding affinity of GNPs was furthermore studied where GNPs of varying linker type, spacer length, ligand density, and nanoparticle size were prepared and K(d) values determined. The long spacer linker containing hydrocarbon and ethylene oxide units gave the highest binding affinity as well as assay sensitivity. The binding affinity increased with ligand density in general, showing a drastic increase in affinity at low ligand density. In addition, the affinity enhancement was more pronounced on smaller NPs than the larger ones. These results not only demonstrate that the binding affinity of GNPs is highly influenced by how the ligands are presented on the nanoparticles, but also pave the way for tailor-made glyconanomaterials with tunable affinity by way of ligand display.